Development of Sporting Capital Measurement - Soner SİVRİ; Oğuz ÖZBEK (ümit doğan üstün, 2023)
Sporting capital is a lately entered term in the literature. Social, psychological and physiological factors are the factors that determine participation in sports. The combination of these three different areas creates the sporting capital of the individual. It is the accumulation of physiological, psychological, and social characteristics and skills motivating the person to do sports, supports and motivates the continuation of the started sport. The purpose of this research is to develop a measurement tool to regulate the sporting capital levels of individuals. Scale dimensions are structured according to sporting capital theory. Physiological, psychological and social fields constitute the dimensions of sporting capital. Quantitative method was used in the research. By examining the relevant literature, a group of questions was created to measure the level of sporting capital. To measure validity, confirmatory factor analysis was implemented by looking at the itemtotal correlation values. Cronbach's Alpha coefficient was calculated for reliability. 334 people, 162 female and 172 male university students, constituted the study group. NFI= .97; RMSEA= ,08; NNFI= ,97; CFI= ,98; GFI= ,90; AGFI= ,85 has been determined in accordance with to the DFA results. Correspondingly, the results of the DFA analysis, it can be said that the fit indices are at an acceptable level. It was observed that Cronbach's Alpha value was 0.92 throughout the scale, and it ranged from 0.70 to 0.88 in the sub-dimensions. These results show that the scale is reliable. Accordingly, it can be concluded that the scale is a valid and reliable measurement instrument in order to define the sporting capital levels of individuals.